1999
DOI: 10.1017/s1047951100008349
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of atrial septal defects under echocardiographic guidance without X-ray: initial experiences

Abstract: We conclude that in selected cases with an atrial septal defect located in the oval fossa and clear-cut echocardiographic findings, an Amplatzer Septal Occluder can be safely deployed under echocardiographic guidance alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…It has even been suggested that ASD closure with the Amplatzer occluder can be carried out under TOE guidance alone. 23 Cobra head malformation of the Amplatzer septal occluder is sometimes difficult to overcome and may prolong the procedure. While it occurred more often in the past with the first generation of Amplatzer devices, it still may happen, particularly if there is not enough space for the configuration of the left or right atrial disc within the left or right atrium in a small patient.…”
Section: Discussionmentioning
confidence: 99%
“…It has even been suggested that ASD closure with the Amplatzer occluder can be carried out under TOE guidance alone. 23 Cobra head malformation of the Amplatzer septal occluder is sometimes difficult to overcome and may prolong the procedure. While it occurred more often in the past with the first generation of Amplatzer devices, it still may happen, particularly if there is not enough space for the configuration of the left or right atrial disc within the left or right atrium in a small patient.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of patients have already undergone placement of devices without fluoroscopy. 23 In conclusion, transesophageal echocardiography is a safe and effective method for evaluating and guiding transcatheter closure of defects within the oval fossa. The examination should be conducted in at least 3 orthogonal planes, paying particular attention to the anterosuperior rim of the defect and the direction of the major axis of the defect.…”
Section: Discussionmentioning
confidence: 95%
“…These changes have reduced the exposure to ionizing radiation, especially during implantation, where fluoroscopic guidance has been replaced to an important degree by transesophageal echocardiography. Ewert et al [5] reported on the use of transesophageal echocardiography only for Amplatzer device placement without fluoroscopy. Despite this bold attempt to eliminate radiation exposure entirely for ASD occlusion, most centers, including ours, continue to use fluoroscopy during ASD sizing and device placement (as an adjunct to transesophageal echocardiography).…”
Section: Discussionmentioning
confidence: 99%